Atosiban Versus Fenoterol as a Uterine Relaxant for External Cephalic Version: Randomized Controlled Trial. Issue 3 (September 2017) - Velzel, J.; Vlemmix, F.; Opmeer, B.C.; Molkenboer, J.F.; Verhoeven, C.J.; van Pampus, M.G.; Papatsonis, D.N.; Bais, J.M.; Vollebregt, K.C.; van der Esch, L.; Van der Post, J.A.; Mol, B.W.; et al.
Abstract : ( BMJ. 2017;356:i6773) Breech presentation occurs in approximately 4% of term singleton pregnancies, and has been reported to be the third most common indication for elective cesarean delivery. External cephalic version (ECV) is a safe procedure that can successfully convert a breech presentation to a cephalic presentation in about 50% of women who undergo the procedure, thereby decreasing the cesarean delivery rate.